Modified Audit Reports in the Case of Joint Municipal Authorities: Empirical Evidence from Finland. Issue 2 (10th March 2016) - Paananen, Mikko
Abstract : This paper explores the determinants of modified audit reports among joint municipal authorities (JMAs) in Finland. Research in this area has traditionally focused on private‐sector corporations, and surprisingly little is known about the practice in municipalities, let alone JMAs. Here is a clear research gap. This study takes the first steps in identifying the determinants of such modifications in Finnish municipal administration. The focus of the analysis is on whether some traditional determinants found among corporations also apply to JMAs. A long audit report lag, audit firm size, and a large organizational size seem to increase the likelihood of a modified audit opinion, whereas high leverage, a large organizational size, and the male gender of the principal auditor increase the likelihood of modified results of the audit .